2008
DOI: 10.1007/s00383-008-2122-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in neonates with esophageal atresia treated over the last 20 years

Abstract: We evaluated the outcome in infants with esophageal atresia (EA) treated in our department over the last two decades. The medical records of 147 infants treated from 1986 to 2005 were reviewed. Patient characteristics, associated anomalies, surgery and complications were recorded. We divided the material into two time-periods: 1986-1995 and 1996-2005; 125 patients or parents were interviewed regarding gastrointestinal function, respiratory symptoms and education. The incidence of major cardiac defects increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
84
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 33 publications
16
84
2
1
Order By: Relevance
“…Mortality, leak and fistula rates were similar to contemporary series [16][17][18][19][20].The current mortality rate of 7.6% compares with a 14% mortality in our previous institutional series (χ 2 = 2.8, P = .09) [21]. Compared with that series, Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Mortality, leak and fistula rates were similar to contemporary series [16][17][18][19][20].The current mortality rate of 7.6% compares with a 14% mortality in our previous institutional series (χ 2 = 2.8, P = .09) [21]. Compared with that series, Fig.…”
Section: Discussionsupporting
confidence: 69%
“…However, there are some other surgeons who favor the ES operation because of the decreased rate of leak and stricture. In 2004, Touloukian and Seashore [13] reported their 35 years of experience with ES repair; and with several key steps (adequate mobilization of the upper pouch, limited circumferential dissection of the lower esophagus at the TEF, fistula ligature to obliterate the lumen, downward displacement of the upper segment with anchoring sutures to the side of the lower esophagus before opening the lumen, and single-layer anastomosis with fine sutures), they decreased the incidence of recurrent TEF to 7%, which was not higher than that in other reports [7,10,14]. In the present study, we mainly performed the ES operation.…”
Section: Discussionmentioning
confidence: 53%
“…12 A literature review has revealed few studies on HRQoL in children with congenital abnormalities and these are mostly from Northern European countries. 1,9,13,14 As QoL is a subjective, multidimensional experience of wellbeing that is culturally constructed more studies are needed to understand HRQoL in children with congenital abnormalities from various communities. 15 We came across only one study from Turkey on the QoL in children with anorectal malformations.…”
mentioning
confidence: 99%